The Potential of Renewable Energy Green Financing through Carbon Taxation to Achieve Net-Zero Emissions Target - Ayodele F.O.; Mustapa S.I.; Ayodele B.V. (Econjournals, 2024)
Climate change is mostly caused by anthropogenic emissions of greenhouse gases like carbon dioxide. By establishing green financing initiatives and levying taxes on carbon pollution, green financing and carbon taxes are seen as viable policy tools for reducing harmful environmental externalities. This study examines the role of carbon taxes as an emerging source of renewable energy green financing to achieve net-zero emissions targets. Raising research questions such as: Can carbon taxation be employed as a means of offsetting carbon emissions? What is the peoples perception of carbon tax? Can carbon taxation be a potential source of green financing for renewable projects? The study established that the implementation of a carbon tax has a significant effect in offsetting carbon emissions to a large extent. However, there are divergent views of people toward the implementation carbon tax as indicated by studies from different countries. The findings established that the revenue generated from carbon tax could be channeled towards the funding of renewable energy projects as obtainable in Japan and other countries. 2023, Econjournals. All rights reserved.